2019
DOI: 10.1021/acs.jpcb.9b07481
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Driven Translocation of a Diblock Copolymer through a Nanopore

Abstract: Using a hybrid molecular dynamic and lattice Boltzmann simulation method, we investigate the flow-driven translocation of a diblock copolymer which is composed of a hydrophilic block and a hydrophobic block through a nanopore. Our results illustrate the nontrivial translocation dynamics of diblock copolymers. We find that the increase in the number of hydrophobic segments requires a larger critical flow rate and a reduced translocation time, which implies that the separation of diblock copolymers with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In the aspect of simulations, we have demonstrated that the enhancement in homopolymer insolubility results in the increase of q c , indicating that as the conformation collapses, the compressibility of the polymer chain becomes worse. 38 For amphiphilic diblock copolymers, we find that the increase in the number of hydrophobic segments results in a larger q c , 40 and such an observation is similar to our study of the homopolymer system. 38 Obviously, in a poor solvent, the interaction energy of insoluble blocks plays a crucial role in determining the deformability of target chains rather than the entropy origin.…”
Section: Progress In Experimental Observation Andsupporting
confidence: 87%
See 3 more Smart Citations
“…In the aspect of simulations, we have demonstrated that the enhancement in homopolymer insolubility results in the increase of q c , indicating that as the conformation collapses, the compressibility of the polymer chain becomes worse. 38 For amphiphilic diblock copolymers, we find that the increase in the number of hydrophobic segments results in a larger q c , 40 and such an observation is similar to our study of the homopolymer system. 38 Obviously, in a poor solvent, the interaction energy of insoluble blocks plays a crucial role in determining the deformability of target chains rather than the entropy origin.…”
Section: Progress In Experimental Observation Andsupporting
confidence: 87%
“…We cannot simply assume that the physical image of the confined copolymer chain is still a series of blobs with the same properties. Our previous simulations have confirmed that for linear diblock copolymers the hydrophobic part is easier to aggregate, resulting in a completely different capture process from that of linear homogeneous polymers . Therefore, how to calculate the free energy barrier of these copolymers in a nanochannel and be able to correlate with the work done by the shearing fluid at the same time is also an important breakthrough direction in the future.…”
Section: Future Research Directionsmentioning
confidence: 92%
See 2 more Smart Citations
“…For two hydrophobic beads, we set the cutoff value to be r c = 2.5s, which is close to the poor solvent condition. 32,33 Meanwhile, for the other pairwise beads, the cutoff is set to be the minimum r c = 2 1/6 s, which is the good solvent condition and corresponds to a purely repulsive LJ potential. 34 Furthermore, all LJ potentials are shifted to satisfy U LJ = 0 at r c .…”
Section: Model and Methodsmentioning
confidence: 99%